Covalent binding of penicillamine to macrophages: implications for penicillamine-induced autoimmunity. - Li, J.; Mannargudi, B.; Uetrecht, J. P.
Idiosyncratic drug reactions (IDRs)represent a major clinical problem, and at present, the mechanisms involved are still poorly understood. One animal model that we have used for mechanistic studies of IDRs is penicillamine-induced autoimmunity in Brown Norway (BN)rats. Previous work in our lab found that macrophage activation preceded the clinical autoimmune syndrome. It is thought that one of the interactions between T cells and macrophages involves reversible Schiff base formation between an amine on T cells and an aldehyde on macrophages, but the identity of the molecules involved is unknown. It is also known that penicillamine reacts with aldehyde groups to form a thiazolidine ring, which unlike a Schiff base, is essentially irreversible. Such binding could lead to macrophage activation. Generalized macrophage activation could lead to the observed autoimmune reaction. Hydralazine and isoniazid also react with aldehydes to form stable hydrazones, and they also cause an autoimmune lupuslike syndrome. In this study, isolated spleen cells from male BN rats were incubated with biotin-aldehyde-reactive probe (ARP, a hydroxylamine), biotin-hydrazide, or D-penicillamine. At all concentrations, ARP, hydrazide, and penicillamine preferentially "stained" macrophages relative to other spleen cells. In addition, preincubation of cells with penicillamine or hydralazine decreased ARP staining of macrophages, which further indicates that most of the ARP binding to macrophages involves binding to aldehyde groups. This provides support for the hypothesis that the interaction between aldehyde-containing signaling molecules on macrophages and penicillamine could be the initial event of penicillamine-induced autoimmunity. Several of the proteins to which ARP binds were identified, and some such as moesin are attractive candidates to mediate macrophage activation.
Keywords: MACROPHAGES; AUTOIMMUNITY